1996
DOI: 10.1021/jp951839h
|View full text |Cite
|
Sign up to set email alerts
|

Ab Initio Computations of the Geometrical, Electronic, and Vibrational Properties of the Ground State, the Anion Radical, and the N,N‘-Dihydro Cation Radical of 4,4‘-Bipyridine Compared to Transient Raman Spectra

Abstract: The geometrical and electronic structures, the force constants, the vibrational frequencies, and the potential energy distributions for various isotopomers of 4,4‘-bipyridine (44BPY) in the ground state S0 and for the corresponding anion radical 44BPY•- and N,N‘-dihydro cation radical 44BPYH2 •+ have been computed by the 3-21G(+*) ab initio method, with the RHF formalism for the ground state S0 and with the ROHF formalism for the ionic species. The theoretical results have been compared to the available vibrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
86
1

Year Published

2000
2000
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 73 publications
(95 citation statements)
references
References 37 publications
8
86
1
Order By: Relevance
“…Even including sufficient diffuse basis functions (aug-cc-pVDZ), the SCF description (both Koopmans theorem and ∆-SCF) is even qualitatively inadequate; the anion is predicted to be unstable. This is already known from earlier work 47,49,50 . As visible in Table 1, we found that electron correlations (which, by definition, measure deviation from SCF) cannot be adequately included via MP2 and the OVGF 21,22 : the 44BPY •− anion remains unstable.…”
Section: Lowest Electron Attachment Energiessupporting
confidence: 57%
“…Even including sufficient diffuse basis functions (aug-cc-pVDZ), the SCF description (both Koopmans theorem and ∆-SCF) is even qualitatively inadequate; the anion is predicted to be unstable. This is already known from earlier work 47,49,50 . As visible in Table 1, we found that electron correlations (which, by definition, measure deviation from SCF) cannot be adequately included via MP2 and the OVGF 21,22 : the 44BPY •− anion remains unstable.…”
Section: Lowest Electron Attachment Energiessupporting
confidence: 57%
“…The physics behind the similarity exhibited by the these numerical results is the following. The twisting angle θ of the 44BPY molecule is determined by the competition between the π-electronic interaction of the pyridyl fragments, which favors π-electrons delocalized between coplanar pyridyl rings (θ = 0), and the steric repulsion between the ortho H atoms, which is diminished by a twisted conformation (θ = 0) [32]. The latter prevails in the neutral species 44BPY 0 (empty/oxidized LUMO), which is nonplanar ( fig.…”
mentioning
confidence: 99%
“…This important shift may be compared to those already observed upon quaternisation of the pyridyl ring, for example on going from pyridine to pyridinium (+47 cm -1 ) 89 or to N-methyl-pyridinium (+49 cm -1 ) 90 or from 44BPY to N,N′-diprotonated cation 44BPYH 2 2 + (+44 cm -1 ) 56 or to N,N′-dihydro cation radical 44BPYH 2 •+ (+55 cm -1 ). 55 Modes 1 and 12 are characterized by a potential energy largely redistributed upon adsorption. The frequencies of both modes are significantly upward shifted on passing from PY to adsorbed PY.…”
Section: (+4)mentioning
confidence: 99%
“…The IR and Raman spectra of crystalline 44BPY have been reported in the literature. [52][53][54][55][56] Table 8 contains our more recent experimental data. 56 Accurate assignments have been obtained by our previous ab initio and B3LYP calculations using 3-21G(+*) and 6-31G(+*) basis sets.…”
Section: Free and Adsorbed 44bpymentioning
confidence: 99%
See 1 more Smart Citation